Builders of the Third Reich : the Organisation Todt and Nazi forced labour - Dick, Charles (Bloomsbury Academic, 2021)
Zusammenfassung: "This is the first comprehensive critical study of the Organisation Todt (OT), a key institution which oversaw the Third Reich's vast slave labour programme together with the SS, Wehrmacht and industry. The book breaks new ground by revealing the full extent of the organisation's brutal and murderous operations across occupied Europe and in the Reich. For the first time, Charles Dick provides a strong voice for camp survivors overseen by the OT, drawing on an extensive collection of personal accounts and analysing the violence they endured"--(Provided by publisher.)